FRUIT CHARACTERISTIC AND NUTRIENT VALUES OF FOUR INDONESIAN BANANA CULTIVARS (Musa spp.) AT DIFFERENT GENOMIC GROUPS - Hapsari, Lia; Lestari, Dewi Ayu (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Aims of this research were to describe the morphology and analyze nutrient values of mature fruits at three different genomic groups of Indonesian banana cultivars including Pisang Berlin (AA), Ambon Hijau (AAA), Raja Bandung (ABB) and Kepok (ABB). Fruit characterization results show that each banana cultivar had specific characteristics related to their genomic group. Pisang Berlin has bright yellow peel and pulp, sugary taste. Pisang Ambon Hijau has fine curved fruit shape, sweet taste and aromatic. Pisang Raja Bandung has medium thickness and yellow peel, firm flesh, sweet and slightly acidic taste. Pisang Kepok has thick coarse and yellow peel with dark brown blotches, mild sweet taste. Fruit characters of Pisang Berlin and Ambon Hijau are close related to their ancestral parentsâ€™ Musa acuminata wild species, whereas Pisang Kepok and Pisang Raja Bandung as hybrid cultivars have intermediate characters between Musa acuminata and Musa balbisiana wild species. Nutrient analysis revealed that mature banana pulp contain of high carbo-hydrates (16.72-35.24 g 100g-1), total sugar (12.12-20.82 g 100g-1), vitamin C (16.45-30.27 g 100g-1) and potassium (275-375 g 100g-1); moderate protein (1.48-1.78 g 100g-1) and low fat (0.03-0.08 g 100g-1). About 100 g edible portion of banana fruit produce 73.43 to 148.80 calories.Â